2017
DOI: 10.20944/preprints201709.0093.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Analysis of Surface Topography of Custom CAD/CAM ZirconiaAbutments by means of Optical Profilometry

Abstract: Objective: CAD/CAM generated ceramic implant abutments have recently attracted interest due to their superior customization possibilities and aesthetic advantages. Despite their widespread clinical use, little information is currently available on their surface topography, however. The transmucosal portion of the abutment shoulder is of particular interest, as it ideally supports soft tissue but minimizes mechanical plaque retention. The aim of this in vitro study was to topographically characterize the trans-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
1
1
0
2
Order By: Relevance
“…Wettability plays an important role in osseointegration, [20,21] and this was clearly supported by our results of the 2D and 3D cell proliferation tests. All surfaces with increased hydrophilic properties showed improved cell proliferation compared with the rather hydrophobic untreated PEEK samples.…”
Section: D Proliferation Tests On Structured and Modified Peeksupporting
confidence: 84%
See 1 more Smart Citation
“…Wettability plays an important role in osseointegration, [20,21] and this was clearly supported by our results of the 2D and 3D cell proliferation tests. All surfaces with increased hydrophilic properties showed improved cell proliferation compared with the rather hydrophobic untreated PEEK samples.…”
Section: D Proliferation Tests On Structured and Modified Peeksupporting
confidence: 84%
“…[18,19] For example, it has been shown that wettability has a strong influence on cellular behavior, and that cells exhibit improved adhesion and proliferation on hydrophilic surfaces. [20,21] The relative hydrophobicity of unmodified PEEK can therefore partially explain its bioinert character [22] and can be overcome through the application of surface modification (SM) methods. Numerous SM techniques have already been explored, such as the deposition of coatings, surface functionalization through the grafting of new chemical groups, and surface patterning.…”
Section: Introductionmentioning
confidence: 99%
“…Es gibt jedoch noch keinen allgemein akzeptierten Standard dafür, wo der Parameter der Rauheit für dentale Werkstoffe endet und die Welligkeit beginnt. Gehrke et al schlagen für eine optimale Weichgewebsintegration (transmukosaler Bereich) von Abutments einen Sa-Wert zwischen 0,21 und 0,4 µm vor (32). Die Stege von ZST (Sa = 0,23 µm), ZDC (Sa = 0,33 µm) und ZCC (Sa = 0,39 µm) liegen in diesen Grenzen und bieten dieser Studie zufolge, bezüglich ihrer Oberfläche, optimale Voraussetzungen für die transmukosale Integration.…”
Section: Profilometrische Beurteilungunclassified
“…9 ROI 1 transmukosaler Bereich, * isotrope Struktur, Δ unregelmäßige Struktur, roter Kreis poliert, ohne Symbol anisotrope Struktur.stärker streuen (SD = ± 0,05 -± 0,15). Dies lässt auf unterschiedliche Bearbeitungsweisen in den Regionen schließen[32].…”
unclassified